The role of educational mobile apps in learning English (non-linguistic specialties) - Assanova, D.N.; Prlepessova, A.B. (KSU Publ., 2020)
The article discusses approaches to effective use of mobile applications in the process of teaching a foreign language, their impact on improving the quality of students' knowledge, ways to effectively implement and test this aspect through non-traditional forms of education. The authors describe the practical significance of using educational mobile applications as a productive component that affects the content of the material, its systematization and assimilation. The relevance of the article is due to the rapid development of mobile applications for teaching foreign languages, the rapid development of the information society, which leads to the obsolescence of traditional technologies for teaching foreign languages, the need to correct them by using mobile applications in the educational process.
Ағылшын тілін оқытудағы білім беру мобильді қосымшаларының рөлі (лингвистикалық емес мамандықтар)
Роль образовательных мобильных приложений в изучении английского языка (нелингвистические специальности)
Keywords: modern information society; information technologies; mobile applications; foreign language; non-linguistic specialties